2005
DOI: 10.2172/888603
|View full text |Cite
|
Sign up to set email alerts
|

DOE Project on Heavy Vehicle Aerodynamic Drag FY 2005 Annual Report

Abstract: In Memory Dr. Sidney ('Sid') DiamondThis document is dedicated to our DOE Program Manager, supporter, and dear friend Dr. Sid Diamond. This Consortium effort would not exist without Sid's vision, dedication, perseverance, and passion. His enthusiasm for this project, with his wonderful gusto for life, was contagious and pushed our effort forward. He will be dearly missed. FY 2005 Annual Report Heavy Vehicle Systems 3 ObjectiveClass 8 tractor-trailers consume 11-12% of the total US petroleum use. At high way sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…This finding is also consistent with previous studies which have shown that drag coefficients can be predicted accurately using steady RANS models but that more complex regions of the flow require careful grid resolution and/or time-dependent turbulence modelling [15,16]. It further highlights the importance of experimental validation data from which the most appropriate turbulence model for a particular geometry can be chosen.…”
Section: Cfd Analysis Of Wind Tunnel Flows: Verification and Validationsupporting
confidence: 91%
“…This finding is also consistent with previous studies which have shown that drag coefficients can be predicted accurately using steady RANS models but that more complex regions of the flow require careful grid resolution and/or time-dependent turbulence modelling [15,16]. It further highlights the importance of experimental validation data from which the most appropriate turbulence model for a particular geometry can be chosen.…”
Section: Cfd Analysis Of Wind Tunnel Flows: Verification and Validationsupporting
confidence: 91%